2022
DOI: 10.1155/2022/7896371
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Circadian Gene Period2 Knockout on Intestinal Metabolism and Hepatic Antioxidant and Inflammation State in Mice

Abstract: The period circadian regulator 2 (Per2) gene is important for the modulations of rhythmic homeostasis in the gut and liver; disruption will cause metabolic diseases, such as obesity, diabetes, and fatty liver. Herein, we investigated the alterations in intestinal metabolic and hepatic functions in Per2 knockout (Per2-/-, KO) and wild-type (Per2+/+, WT) mice. Growth indices, intestinal metabolomics, hepatic circadian rhythms, lipid metabolism, inflammation-related genes, antioxidant capacity, and transcriptome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The TTFL is responsible for maintaining the oscillation system and synchronizing the cycle with the environment. In TTFL regulation, the core clock gene, PER1, acts as a transcriptional repressor, while CLOCK functions as an enhancer that can promote rhythmic activities 24,25 . We found that Fpn1 Cdh5 ‐cKO mice with declined brain iron levels exhibit decreased expression of Per1, with elevated CLOCK levels.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The TTFL is responsible for maintaining the oscillation system and synchronizing the cycle with the environment. In TTFL regulation, the core clock gene, PER1, acts as a transcriptional repressor, while CLOCK functions as an enhancer that can promote rhythmic activities 24,25 . We found that Fpn1 Cdh5 ‐cKO mice with declined brain iron levels exhibit decreased expression of Per1, with elevated CLOCK levels.…”
Section: Introductionmentioning
confidence: 81%
“…In TTFL regulation, the core clock gene, PER1, acts as a transcriptional repressor, while CLOCK functions as an enhancer that can promote rhythmic activities. 24,25 We found that Fpn1 Cdh5 -cKO mice with declined brain iron levels exhibit decreased expression of Per1, with elevated CLOCK levels. These results imply that alterations in brain iron levels can indeed alter circadian clock gene expression and lead to modified TTFL regulation.…”
Section: Introductionmentioning
confidence: 85%
“…31,32 In fact, PER2 expression decreased malignant behavior in several cancers of epithelial origin, such as colorectal, oral, and prostate cancers. 31,[33][34][35][36][37][38][39][40] However, some authors also demonstrated reduced PER2 expression in melanoma and nevus when compared to adjacent nontumor samples. At the molecular level, PER2 expression suppresses MMP-1 expression in human keratinocytes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Per1 also interacts with GPX1 to mediate mitochondrial function and metabolic homeostasis in response to the oxidation process ( 48 ). Moreover, intestinal metabolic dysregulation and hepatic inflammation could be induced by disrupted circadian rhythmic stasis ( 49 ). It is worthwhile to investigate further how valine affects the molecular clock and metabolic health.…”
Section: Discussionmentioning
confidence: 99%